#MeToo in Sweden: A Legal Game-Changer on Sexual Harassment - Sherry Amara Budianjani; Hermini Susiatiningsih; Muhammad Faiq Adi Pratomo (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2025)
Sweden is well-known for having the highest levels of gender equality. In reality, Sweden has one of the highest reported incidences of sexual harassment in the European Union. Numerous feminist movements have arisen as a result, with the #MeToo movement and the Harvey Weinstein case being highly well-known in 2017. As one of the social movements, #MeToo aims to accomplish certain objectives. For example, it is now working to change sexual harassment laws in Sweden. This poses the question, how can a social movement such as #MeToo impact a nation's laws to the extent that those laws have impacted? In this essay, we aim to give a broad overview of a social movement that has garnered a lot of support from Swedish society. The approach is qualitative and uses the theory of liberal feminism and social movement in addition to secondary data collection. The study's findings examine a social movement that urged the government to transform the status quo by providing a safe space for women to fight for gender equality. This movement ultimately resulted in the passing of a new law that was a reform that benefited the victims. Keywords: Social Movement; #MeToo; Sexual Harassment; Policy Change; Sweden.